Sialorrhea in children with cerebral palsy - Bruno Leonardo Scofano Dias; Alexandre Ribeiro Fernandes; Heber de Souza Maia Filho (Elsevier, 2016)
Objective: To review the literature on sialorrhea in children with cerebral palsy. Source of data: Non-systematic review using the keywords "sialorrhea" and "child" carried out in the PubMed®, LILACS®, and SciELO® databases during July 2015. A total of 458 articles were obtained, of which 158 were analyzed as they were associated with sialorrhea in children; 70 had content related to sialorrhea in cerebral palsy or the assessment and treatment of sialorrhea in other neurological disorders, which were also assessed. Data synthesis: The prevalence of sialorrhea is between 10% and 58% in cerebral palsy and has clinical and social consequences. It is caused by oral motor dysfunction, dysphagia, and intraoral sensitivity disorder. The severity and impact of sialorrhea are assessed through objective or subjective methods. Several types of therapeutic management are described: training of sensory awareness and oral motor skills, drug therapy, botulinum toxin injection, and surgical treatment. Conclusions: The most effective treatment that addresses the cause of sialorrhea in children with cerebral palsy is training of sensory awareness and oral motor skills, performed by a speech therapist. Botulinum toxin injection and the use of anticholinergics have a transient effect and are adjuvant to speech therapy; they should be considered in cases of moderate to severe sialorrhea or respiratory complications. Atropine sulfate is inexpensive and appears to have good clinical response combined with good safety profile. The use of trihexyphenidyl for the treatment of sialorrhea can be considered in dyskinetic forms of cerebral palsy or in selected cases. Resumo: Objetivo: Revisar a literatura referente a sialorreia em crianças com paralisia cerebral. Fonte de dados: Revisão não sistemática utilizando as palavras-chave "sialorreia" e "criança" realizada nas bases de dados Pubmed®, Lilacs® e Scielo® em julho de 2015. Foram recuperados 458 artigos, 158 foram analisados por terem relação com sialorreia em crianças, 70 com conteúdo relativo à sialorreia na paralisia cerebral ou a avaliação e tratamento da sialorreia em outros distúrbios neurológicos foram aproveitados. Síntese dos dados: A sialorreia tem prevalência entre 10% e 58% na paralisia cerebral e implica em consequências clínicas e sociais. É causada por disfunção motora oral, disfagia e distúrbio da sensibilidade intraoral. A gravidade e o impacto da sialorreia são avaliados através de métodos objetivos ou subjetivos. Estão descritas diversas formas de manejo terapêutico: treino para consciência sensorial e habilidades motoras orais, terapia farmacológica, injeção de toxina botulínica e tratamento cirúrgico. Conclusões: O tratamento mais eficaz e que aborda a causa da sialorreia nas crianças com paralisia cerebral é o treino para consciência sensorial e habilidades motoras orais, realizado por um fonoaudiólogo. Injeção de toxina botulínica e o uso de anticolinérgicos têm efeito transitório e são auxiliares ao tratamento fonoaudiológico ou devem ser consideradas nos casos de sialorreia moderada a grave ou com complicações respiratórias. O sulfato de atropina tem baixo custo e parece ter boa resposta clínica com bom perfil de segurança. O uso de triexifenidil para o tratamento da sialorreia pode ser considerado nas formas discinéticas de paralisia cerebral ou em casos selecionados. Keywords: Sialorrhea, Cerebral palsy, Child, Palavras-chave: Sialorreia, Paralisia cerebral, Criança